Lateral genicular artery flap for reconstruction of defects around the knee: a series of 5 cases - Mahipathy, Surya Rao Rao Venkata; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Jayachandiran, Anand Prasath (International Surgery Journal, 2020)
The lateral genicular artery flap is a fasciocutaneous flap used for knee reconstruction with low donor site morbidity. It is raised from the lower lateral thigh and is based upon the cutaneous termination of superior lateral genicular artery. This flap showed constant anatomy and is reliable for coverage of defects at superior and lateral portions of the knee and the proximal part of the lower leg. The study period was from January 2016 to June 2017 where we operated on 5 patients, 3 for post-traumatic and 2 were post burn contracture excision. The flap was used as a pedicled fasciocutanous and was based on the superior lateral genicular artery. Five cases underwent lateral genicular artery flap of which 4 were males and 1 was a female. Mean defect size was 12 cm×10 cm. All the donor sites were closed with a split skin graft. One patient had distal necrosis which was managed conservatively. The lateral genicular artery flap is a thin, versatile, reliable and easy to harvest flap for reconstructing defects around the knee, with good cosmetic and functional outcome.